2019
DOI: 10.1177/2164956119844151
|View full text |Cite
|
Sign up to set email alerts
|

Application of Manual Therapy for Dysphagia in Head and Neck Cancer Patients: A Preliminary National Survey of Treatment Trends and Adverse Events

Abstract: Background Radiation-associated dysphagia is a common and debilitating consequence of treatment for head and neck cancer (HNC). Since commonly employed dysphagia therapy programs for HNC patients still lack authoritative efficacy, some speech-language pathologists (SLPs) have started employing manual therapy (MT) techniques in an attempt to prevent or rehabilitate dysphagia in this patient population. However, exceptionally little is known about the use of MT in this patient population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In particular, manual therapy has been associated with improved blood circulation, reduced muscle spasms, increased ROM, the release of connective tissue adhesions, reduced pain and restoring mobility [ 17 , 18 ]. Specifically, in survivors of HNC manual therapy showed no specific adverse outcomes [ 19 ], reporting adverse events similar to those experienced by patients without cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, manual therapy has been associated with improved blood circulation, reduced muscle spasms, increased ROM, the release of connective tissue adhesions, reduced pain and restoring mobility [ 17 , 18 ]. Specifically, in survivors of HNC manual therapy showed no specific adverse outcomes [ 19 ], reporting adverse events similar to those experienced by patients without cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAD should be prevented to minimize the effects on the quality of life of HNC patients. Few effective treatments are available for HNC patients with RAD, including postural rehabilitation [ 10 , 11 ] Krisciunas et al [ 10 ] demonstrated that SLPs provide Manual Therapy(MT) to HNC patients during and after cancer treatment, and that reported adverse events paralleled those experienced by noncancer patients. National Cancer institute-funded prospective single-arm pilot trial called Manual Therapy for Fibrosis-Related Late Effect Dysphagia (MANTLE) is going on, which is evaluating the feasibility, safety and therapeutic potential of MT in patients with late dysphagia after radiotherapy for HNC [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cervical radiation-induced fibrosis (RIF) can lead to strap muscle fibrosis, impairing laryngeal elevation and causing RAD in HNC survivors [ 9 ]. Currently, the only effective treatment for RAD is rehabilitation [ 10 , 11 ]. Moreover, no functional or histological assays are available for the evaluation of RIF of strap muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Manual therapies, targeting swallow musculature through passive and active stretching and soft muscle mobilisation, may offer a potential treatment to mitigate some of the long-term effects associated with radiation-induced fibrosis. In the USA, there is evidence of clinical application despite only speculative evidence for its effectiveness with patients with HNC [ 75 ]. Preliminary findings suggest manual therapies, often reserved as a reactive intervention for lymphedema, may in fact be tolerable and actually reduce localised pain during radiotherapy in this population [ 76 ].…”
Section: Speech and Language Pathology Interventionsmentioning
confidence: 99%